2018
DOI: 10.1002/2017gl075711
|View full text |Cite
|
Sign up to set email alerts
|

Magnetospheric Multiscale Observations of Electron Scale Magnetic Peak

Abstract: The sudden enhancements of magnetic strength, named magnetic peaks (MPs), are often observed in the magnetosheath of magnetized planets. They are usually identified as flux ropes (FRs) or magnetic mirror mode structures. Previous studies of MPs are mostly on the magnetohydrodynamics (MHD) scale. In this study, an electron scale MP is reported in the Earth magnetosheath. We present a typical case with a scale of ~7 electron gyroradii and a duration of ~0.18 s. A strong magnetic disturbance and associated electr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
55
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 39 publications
(58 citation statements)
references
References 78 publications
2
55
1
Order By: Relevance
“…recent MMS observations near the magnetopause report electron scale magnetic enhancements (Yao et al, 2018), although the behavior of E is not examined.…”
Section: 1029/2018gl079095mentioning
confidence: 98%
See 1 more Smart Citation
“…recent MMS observations near the magnetopause report electron scale magnetic enhancements (Yao et al, 2018), although the behavior of E is not examined.…”
Section: 1029/2018gl079095mentioning
confidence: 98%
“…Magnetic enhancements associated with small‐scale current loops have not been as extensively discussed in the literature. However, recent MMS observations near the magnetopause report electron scale magnetic enhancements (Yao et al, ), although the behavior of E is not examined.…”
Section: Small‐scale Substructurementioning
confidence: 99%
“…Many of these key processes involve kinetic‐scale physics. With measurements of high‐temporal cadence from the Magnetospheric Multiscale (MMS) mission (Burch et al, 2016), the KSMDs and some possible related structures were reported in the turbulent magnetosheath (Huang, Sahraoui, et al, ; Yao et al, ; Yao, Shi, Guo, et al, ) and are thought to play an important role in dissipating energy (Huang, Sahraoui, et al, ). In addition, from recent two‐ and three‐dimensional particle‐in‐cell simulations, the KSMDs were found in turbulent magnetized plasmas (Haynes et al, ; Roytershteyn et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have revealed that the mirror-mode structures are generated in high plasma beta (the ratio of the plasma pressure to the magnetic pressure) regions, with the perpendicular plasma pressure being greater than parallel plasma pressure. They were also often considered a possible source of magnetic dips in many studies (e.g., Ahmadi et al, 2017;Horbury et al, 2004;Joy et al, 2006;Shi et al, 2009;Xiao et al, 2014;Zhang et al, 2008), though different mechanisms were proposed by others (e.g., Balikhin et al, 2012;Ji et al, 2014;Li et al, 2016;Yao et al, 2016Yao et al, , 2017Yao et al, , 2018. Furthermore, their spatiotemporal scales and evolution processes, three-dimensional (3-D) structures, and other important kinetic effects (e.g., drift, finite Larmor radius effect, non-Maxwellian ion distribution, and electron temperature influence) were also extensively investigated (e.g., Ahmadi et al, 2016;Chisham et al, 1998;Feygin et al, 2009;Gary & Karimabadi, 2006;Gedalin et al, 2001;Genot et al, 2009;Hasegawa, 1969;Hellinger et al, 2009;Klimushkin & Chen, 2006;Pokhotelov et al, 2013;Pokhotelov & Pilipenko, 1976;Treumann et al, 2004).…”
Section: Introductionmentioning
confidence: 99%